PERSEKTIF QUR’ANI TENTANG KEMANUSIAAN DAN KESETERAAN GENDER : Studi Teks terhadap Nilai-Nilai Hak Asasi - Muhammad Raihan Syahid; Sholahuddin Al ayubi (CV. Adiba Aisha Amira, 2025)
The discourse on human rights and gender equality has become a major theme in contemporary religious and social studies. This research explores the representation of human dignity and gender justice values in the Qur’an as a normative Islamic ethical foundation for human rights. Employing a thematic exegesis (maudhū‘ī) method combined with critical hermeneutics and a contextual-interpretative approach, this study systematically analyzes relevant Qur’anic verses to uncover meanings aligned with modern social ethics. It also critically compares the perspectives of scholars such as Abdullahi An-Na'im, Amina Wadud, and Fazlur Rahman in integrating human rights into Islamic theology. The findings reveal that the Qur’an strongly upholds the principles of universal justice, protection of human dignity, freedom of belief, and gender equality, emphasizing piety and social accountability. This study contributes a constructive Qur’anic synthesis that offers inclusive and progressive interpretations relevant to current debates on social and gender justice.